Nemzeti Területfejlesztési Koncepció: rövidített változat - Barta, Györgyi; Csefkó, Ferenc; Faragó, László; Horváth, Gyula; Hrubi, László; Illés, Iván; Pálné Kovács, Ilona; Rechnitzer, János (Tér és Társadalom, 1995)
The Centre for Regional Studies of the Hungarian Academy of Sciences, on commission of the Ministry of Environmental Protection and Regional Development, has carried out a study for the scientific establishment of the Hungarian Regional Development Concept. The study consists of almost 100 pages. The editorial of the journal has created and published its abbreviated version in order to enable the professional discussion of the government document that is of basic importance for the regional policy of Hungary in the future. The essay, like possibly the Concept itself, starts with the evaluation of the regional processes and regional policy of the past era. The essay states that the transition of the ownership, organisation and structure of the economy after the systemic change has resulted in significant regional differences compared to the former mechanism of the socialist economy, which attempted to reach regional equality. Following the systemic change infrastructure showed a significant (although in sectoral approach, uneven) development, especially in the field of water supply and telecommunication infrastructure, while no development or change took place in the spatial structure of transport infrastructure that is extremely important for moderniration. The capacity of primary and secondary education increased. In general we can say that the infrastructure developments supported by the government mainly favoured small settlements in the last few years. In employment and the income of the population considerable regional disparities emerged, showing the borders of some crisis regions. Social changes had the most dramatic consequences in the villages. The regional policy of the past era definitely focused on crisis regions, its institutional system was centralised and the implementation of the different sectoral programmes was not harmonised. The second chapter of the study discusses the medium ad long term objectives of regional development, its tasks and tools, also, the basic elements of the new model of regional policy. It is a fundamental change that the primary objective of regional policy is supporting economic development, in the second place of course it aims to decrease social and economic inequality of chances and to manage crisis situations. A dominant change is the appreciation of the role of local resources and the criteria of integrating into the European regions. In the transition of the economic structure the following elements have key importance: Desindustrialisation, tertierisation, change of technology, decentralisation and the criteria of sustainable development. Regional policy in Hungary in the future will assert the principles of subsidiarity, decentralisation, partnership, programming, concentration and additionality during the creation of its structure of institutions. The chapter evaluating the present situation ends with enumerating the strengths and weaknesses, the opportunities and threats of the former regional policy. Among the possibilities of regional policy the authors put great stress on the adoption of a decentralised system of institutions and tools and that of regionalism, also, European integration. After this the essay analyses the external conditions of Hungarian regional development, the possible scenarios that say regional development in Hungary can evolve towards polarised, relatively deconcentrated and decentralised development, as a function of the actual internal and external conditions. The essay talks about the expectations towards the operation of the system of regional development institutions now taking shape in Hungary, consistently sticking to the necessity of decentralisation. After the act on regional development coming into force, among the financial tools of regional policy the role of the Regional Development Fund is appreciated. At the same time, the work also describes the necessity of the further development of the general financial regulation so that state sources can be used in a more co-ordinated way, taking regional development objectives into consideration. The essay dedicates a separate chapter to the types of regions deserving special attention, the regions of intervention of regional policy. One dimension of division is the designation of the certain regions by type of the problem: The capital city and its agglomeration, the pole regions of economic innovation, border regions, regions underdeveloped in economic and social sense, industrial depression regions, rural regions struck by high unemployment, regions in need of special treatment because of environmental reasons, and entrepreneurial zones. By using another regional dimension, the essay discusses the main characteristics and the development tasks of the large regions of Hungary (Northern Great Plain, Southern Great Plain, Northern Hungary, Northern Transdanubia, Southern Transdanubia and the central district), considering the formation of the regions as a topical tasks especially because of the European integration. As a third regional dimension the essay defines the principles of the development of the specific elements of the seftlement network, in a breakdown by capital city, large city, county seat, other towns, villages, small villages and scattered farms. The authors do not link the implementation of the regional policy objectives exclusively to the tools of regional policy: They emphasise the effect of sectoral policies on regional development, as well. They list the regional priorities to be followed by the sectoral policies: Agrarian and industrial policy, energy and tourism policy, employment policy, social and housing policy. The essay is a product of the work group of the Centre for Regional Studies and a few other institutions, with the leadership of Iván Illés director general. Its approach, principles and suggestions will hopefully be fully utilised by the Hungarian Regional Development Concept, to be accepted by a Parliament decision.